Penguatan Harvest Strategy Perikanan Tuna Tropis di Perairan Kepulauan Indonesia: Analisis Data Perikanan di Wilayah Pengelolaan Perikanan 713, 714 dan 715 - Efendi, Diding Sudira; Juniar, Rista Devi; Nurhaidin (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2025)
Indonesian archipelagic waters, including the Fisheries Management Areas (FMAs) 713, 714 and 715, have significant potential for tropical tuna fisheries. The government has prepared harvest strategies to optimize the utilization of these tuna species such as skipjack (SKJ), yellowfin tuna (YFT), and bigeye tuna (BET) in these waters. This paper aims to provide an overview of the characteristics of these fisheries in Indonesian archipelagic waters based on a descriptive analysis of fishing logbook and observer program data received by the Ministry of Marine Affairs and Fisheries. The study shows that during the 2019-2021 period the number of purse seine (PS) trips was relatively stable while hand line (HL) and pole and line (PL) tended to increase. In 2021, the catch composition of PS was dominated by SKJ (73%) and YFT (27%). PL caught SKJ 83% and YFT 17%, while HL's catch was significantly comprised of YFT (95%), BET (2%), and SKJ (3%). BET was predominantly distributed in FMAs 714 and 715, whereas the fishing grounds for YFT closely resembled those for SKJ. The results also provided information that the size composition of tuna species varied based on the fishing gears operated. The mean length of each species caught by PS was smaller than other gears, namely SKJ at 36.9 cm, YFT at 40.22 cm, and BET at 52.87 cm. Therefore, immediate management actions are needed to prevent juvenile capture in the area to ensure the sustainability of tropical tuna fisheries.